Integrating network pharmacology and experimental verification to decipher the immunomodulatory effect of Bu-Zhong-Yi-Qi-Tang against poly (I:C)-induced pulmonary inflammation - Hu, Liufang; Yamamoto, Marina; Chen, Jiali; Duan, Huifang; Du, Jing; He, Liangliang; Shi, Danfeng; Yao, Xinsheng; Nagai, Takayuki; Kiyohara, Hiroaki; Yao, Zhihong (Frontiers in Pharmacology, 2022)
Pulmonary inflammation caused by respiratory tract viral infections is usually associated with acute exacerbation of respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Therefore, maintaining the pulmonary immune homeostasis is particular important for prevention of the acute exacerbation. Bu-Zhong-Yi-Qi-Tang (BZYQT), a traditional Chinese medicine formula, has been broadly used to improve respiratory and gastrointestinal disorders in China for over 700 years. Previously, we have found the regulatory activity of BZYQT on the lower respiratory immune system, while its potential effects during pulmonary inflammation remain unknown. Thus, the current study focused on deciphering its immunomodulatory effect and potential mechanism against pulmonary inflammation by using a viral RNA analogue, poly(I:C), induced murine pulmonary inflammation model and BEAS-2B cell model coupled with network pharmacology. Inflammatory cells in the bronchoalveolar lavage fluid were counted through microscope examination according to the cell’s morphology and staining characteristics; protein and gene levels of inflammatory mediators were determined with Elisa and quantitative PCR, respectively; network pharmacology was conducted based on 46 BZYQT-related potential bioactive components, pulmonary inflammation and immune-related targets. Our results indicated that the recruitment of neutrophils and the expression of Adgre1 (encoding the F4/80, which is a macrophage marker) in the lung induced by poly(I:C) were significantly reduced after BZYQT treatment, and these effects were further demonstrated to be related to the interference of leukocyte transendothelial migration from the decreased levels of CXCL10, IL-6, TNF-α, CXCL2, ICAM-1, VCAM-1, and E/P-selectins. Furthermore, BZYQT inhibited the CXCL10, TNF-α, and IFN-β expression of poly(I:C)-challenged BEAS-2B cells in a dose-dependent manner. Through integrating results from network pharmacology, experiments, and the published literature, isoliquiritigenin, Z-ligustilide, atractylenolide I, atractylenolide III, formononetin, ferulic acid, hesperidin, and cimigenoside were presumed as the bioactive components of BZYQT against pulmonary inflammation. Overall, our findings demonstrated that BZYQT possesses a pronounced immunomodulatory effect on poly(I:C)-induced pulmonary inflammation, which provides a pharmacological basis for BZYQT in the treatment of respiratory disorders.